Gender stereotypes in help-giving and help-seeking - Xu XiaoJin (SHS Web of Conferences, 2023)
The study looked at how prosocial conduct is impacted by gender stereotypes, and it also explores the influence of gender stereotypes on women’s and men’s help-seeking behaviors. The findings suggest that gender stereotypes may act as barriers to prosocial behavior, which in turn affects how people help gender-specific groups. From the point of view mentioned, for the act of offering help, people should give the appropriate help according to the actual situation of the victim, without considering only their gender. This means discarding gender stereotypes and providing tailored help based on individual needs and circumstances. This philosophy can help people to see and solve problems more objectively in practice. These factors may affect people’s attitudes and behaviour towards victims of domestic violence and their need for help. Examining these issues can help researchers better understand gender dynamics in domestic violence and provide a reference for more effective support and help. In conclusion, gender stereotypes have some influence on prosocial behavior. Future research could further explore the impact of education level and cultural factors on gender stereotypes and prosocial behaviors in the circumstance of domestic violence to advance researchers’ knowledge and understanding of this area.